Improving Education and Care in Student-Run Clinics: A Didactic Intervention for Pre-Clinical Medical Students - Andrew Phillips; Sandy G Smith; Rita Rossi-Foulkes; Kristine K Bordenave (Journal of Student-Run Clinics, 2017)
Background: Merging education with clinical care is essential at student-run clinics.Methods: First year medical students participated in 15-minute small-group didactic sessions monthly from January through May 2011. Topics included diabetes, hypertension, mood disorders, and back pain. After the intervention, a 10-question survey comprised of eight 7-point Likert items and two narrative response questions was made available online to all eligible students. Patient encounter times during the intervention period were recorded and compared to the year prior to intervention.Results: Fourteen of 26 students (54%) responded to the survey. All students found the intervention to offer more information about standards of practice than their courses. Of respondents, 64.3% agreed or strongly agreed they provided better patient care with the intervention. Students reported a higher probability of using standards of practice: 57.1% agreed and 21.4% strongly agreed. When accounting for confounders, mean patient encounter time was 69.9 (95%CI, -92.4 to -39.4, p<0.001) minutes shorter with the intervention.Conclusions: Decreased patient encounter time and survey responses support the intervention’s educational and clinical efficacy.